NUTRITIONAL EVALUATION IN UNIVERSITY STUDENTS AND OF AN OPTIMAL DIET AS A MEASURE TO PREVENT COVID-19 - Ruiz-López, Liliana; Felipe-Ortega-Fonseca, Ximena; Vázquez-Curiel, Rosa; Balderrama Carmona, Ana Paola (Horizonte Sanitario, 2021)
Objective: To evaluate the nutritional status of university students to propose the appropriate diet recommendationsMaterials and Methods: The participating students were evaluated by means of a cross-sectional study, by feeding and symptoms surveys; the anthropometric evaluation and the taking of blood samples were carried out under standardized ethical regulations. Statistical analysis was performed by multifactorial logistic regression analysis using the EPI INFO TM. A review of the literature was developed in a database where the appropriate nutrients to prevent COVID-19 are described.Results and discussion: A group of university students (n = 42) between 18 and 22 years old was evaluated. More than 95% of the young people declared consuming carbohydrates as their major food source, on the other hand, 76% showed a BMI within normal parameters (19-24.9 Kg /m2). Low hemoglobin counts were estimated with a prevalence of 11.90% among the participating group.Conclusions: Food remains the key to human health and well-being. Consumption of phytochemicals and nutraceuticals can prevent and even treat SARS-CoV-2 infection. Among the foods with the greatest potential for the prevention of COVID-19 are nuts, eggs, fish, green leafy vegetables, and whole grains. The consumption of phytochemicals and nutraceuticals can prevent and even treat SARS-CoV-2 infection.